Mengoptimalkan Efisiensi Pengangkutan Sampah di Kota Langsa, Indonesia: Pendekatan Dynamic Programming - Muhammad Nizar; Al-Fataya Zikrillah; Arief Rahman; Erdiwansyah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
As the population grows every year, it creates environmental problems, one of which is waste. Langsa City is one of the cities that is not free from these problems. This is shown by the piles of garbage that are not collected in the streets of Langsa City due to the limited transport fleet that has to be rotated with different drivers and teams every shift. The purpose of this research is to find out the efficient time and distance travelled on the waste transport route in Langsa City using the Dynamic Programming method and to find out how efficient the route is in terms of time and fuel cost. Data was collected through observation and interviews. Observations were made of six fleets on each route. For the waste transport routes in Langsa City, after using the Dynamic Programming method, a reduction in mileage of 0.2-2.9 km with time savings of 2-19 minutes was observed. The fuel savings after Dynamic Programming is 0.903% for one shift for all vehicles. This shows that the use of Dynamic Programming to solve the problem of waste transport routes in Langsa City has proven to be effective.